Leadership Influence in Times of Change: A Social Network Perspective - Pallotti, Francesca; Mascia, Daniele; Mühlemann, Neela S. (Personnel psychology, 2025)
ABSTRACT Successful organizational change often depends on network leaders—organizational members who act as informal change agents by exerting influence through their social networks. Integrating a social identity model with a social network perspective, we identify two distinct network leadership roles: Domain Experts and Boundary Spanners. We examine how their relational behaviors facilitate employees’ identification with their work unit during periods of change. We hypothesize that social proximity to both Domain Experts and Boundary Spanners is positively associated with stronger employee identification. Moreover, we argue that the influence of Domain Experts is amplified when change significantly disrupts employees’ daily tasks, whereas the influence of Boundary Spanners becomes more salient when change affects the broader functioning and dynamics of the unit. Understanding how different network leadership roles facilitate identification processes is critical to enabling successful organizational change. Our final hypothesis proposes that higher average levels of employee identification within a unit are positively associated with that unit's effectiveness in implementing change. We test our hypotheses in a multi‐source study of 161 physicians across 29 work units in a large university hospital undergoing major organizational restructuring. The findings support our theoretical model and offer novel insights into the interplay among leadership, social identity, and social networks during organizational transformation.